2008
DOI: 10.1021/jf073181y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Pattern Volatiles and the Overall Aroma of Wild Edible Mushrooms

Abstract: Volatile and semivolatile components of 11 wild edible mushrooms, Suillus bellini, Suillus luteus, Suillus granulatus, Tricholomopsis rutilans, Hygrophorus agathosmus, Amanita rubescens, Russula cyanoxantha, Boletus edulis, Tricholoma equestre, Fistulina hepatica, and Cantharellus cibarius, were determined by headspace solid-phase microextraction (HS-SPME) and by liquid extraction combined with gas chromatography-mass spectrometry (GC-MS). Fifty volatiles and nonvolatiles components were formally identified an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
72
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 34 publications
2
72
1
3
Order By: Relevance
“…The aroma compounds in shiitake mushroom have been identified as eight-carbon compounds and sulfur compounds (Pinho et al, 2008;Thomas, 1973;Maggi et al, 2012). It has been reported that a significant amount of aroma compounds present in fresh mushroom is lost during drying.…”
Section: Volatilesmentioning
confidence: 99%
“…The aroma compounds in shiitake mushroom have been identified as eight-carbon compounds and sulfur compounds (Pinho et al, 2008;Thomas, 1973;Maggi et al, 2012). It has been reported that a significant amount of aroma compounds present in fresh mushroom is lost during drying.…”
Section: Volatilesmentioning
confidence: 99%
“…All the samples extractions were carried out in triplicate. The chromatographic analysis was performed on a Shimadzu GC-2010 Plus equipped with a Shimadzu GCMS-QP2010 SE detector (Malheiro et al, 2017(Malheiro et al, , 2013Pinho et al, 2008). A TRB-5MS (30 m × 0.25 mm × 0.25 μm) column (Teknokroma, Spain) was used.…”
Section: Phenolic Compounds Determinationmentioning
confidence: 99%
“…with those in the other mushroom groups indicated that the volatiles found in this Gasteromycetidae were almost exclusively formed from fatty acids. Terpenoids and ester compounds, such as hexyl acetate and ethyl caproate, that are typical of other mushrooms 1,[18][19][20] were not identified in this study. Even though Astraeus spp.…”
mentioning
confidence: 66%
“…Their culinary and commercial value is mainly due to flavor, which is characteristic of and unique to mushroom species. 1) Among the diverse volatile compounds in mushrooms, aliphatic eightcarbon (C 8 ) components, including 1-octen-3-ol, 2-octen-1-ol, 3-octanol, 1-octanol, 1-octen-3-one, and 3-octanone, have been reported to be major contributors to mushroom flavor. [1][2][3] Astraeus species, ectomycorrhizal fungi, grow in association with tree roots, and their fruiting bodies develop just beneath the soil surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation